2015
DOI: 10.1021/jacs.5b06195
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Fluorescent Host–Guest Complexes with Tunable Color upon Encapsulation

Abstract: Unlike previous coordinative host-guest systems, highly emissive host-guest complexes (up to Φ(F) = 0.5) were successfully prepared upon encapsulation of various fluorescent dyes (e.g., BODIPY and coumarin derivatives) by a Pt(II)-linked coordination capsule in water. Picosecond time-resolved spectroscopy elucidates the photophysical behaviors of the obtained complexes. Notably, the emission color of the fluorescent guest within the capsule can be readily modulated upon pairwise encapsulation with planar aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(89 citation statements)
references
References 34 publications
1
88
0
Order By: Relevance
“…1c), on the basis of our previous synthesis of M 2 L 4 polyaromatic capsules252627282930. We expected that the W-shaped polyaromatic ligands assemble into an M 3 L 4 double capsule ( 2 ) upon complexation with square-planar metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…1c), on the basis of our previous synthesis of M 2 L 4 polyaromatic capsules252627282930. We expected that the W-shaped polyaromatic ligands assemble into an M 3 L 4 double capsule ( 2 ) upon complexation with square-planar metal ions.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination capsules prepared from derivatives of phenylanthracen molecules linked by Pt(II) can co-encapsulate BODIPY with coumarin 153 or Nile red. These structures indicated that the emission color of the fluorescent guest within a cavity of such capsules was readily modulated upon pairwise encapsulation with planar aromatic molecules [111]. The encapsulated complex enclosed by the shell having Pt (II)-phenylanthracen demonstrated the guest-guest interaction within synthetic molecular host-capsules.…”
Section: Photosensitizers As Selective Therapeutic and Imaging Agentsmentioning
confidence: 93%
“…These highly emissive dyes, which are derivatives of 4,4'-difluoro-4-bora-3a,4a-diaza-s-indacene (hereafter abbreviated to BODIPY; boron-dipyrromethane) have been widely utilized in various polymers [101][102][103] because they tend to be strongly UVabsorbing small molecules and emit relatively sharp fluorescence peaks with high quantum yields. This system provides the framework for more elaborate receptors to detect other analytes [104,105]. The comprehensive review summarizing the basic chemistry and spectroscopic properties common BODIPY-derivatives probes intended to intracellular imaging was prepared by Burgess et al [101].…”
Section: Photosensitizers As Selective Therapeutic and Imaging Agentsmentioning
confidence: 99%
“…Recently, Yamashina and Yoshizawa et al found that Pt(II)-linked capsule 4 can quantitatively encapsulate hydrophobic fluorescent dyes such as BODIPY derivative 12, coumarin 153, and Nile red in water. 20 The obtained hostguest complexes showed strong green, bluish-green, and red fluorescence (Φ F = 2548%), respectively (Figure 10a), derived from the corresponding encapsulated dyes. Time-resolved fluorescence measurements revealed that long-lived fluorescence (7.4 ns) is observed from 4¸12 when the guest is directly excited by irradiation at the absorption band.…”
Section: ¹2mentioning
confidence: 99%